Adaptive Action: Leveraging Uncertainty in Your Organization - Eoyang, Glenda H.; Holladay, Royce J. (Stanford University Press, 2013)
Rooted in the study of chaos and complexity, Adaptive Action introduce s a simple, common sense process that will guide you and your organiza tion into reflective action. This elegant method prompts readers to en gage with three deceptively simple questions: What? So what? Now what? The first leads to careful observation. The second invites you to tho ughtfully consider options and implications. The third ignites effecti ve action. Together, these questions and the tools that support them p roduce a dynamic and creative dance with uncertainty. The road-tested steps of adaptive action can be used to devise solutions and improve p erformance across multiple challenges, and they have proven to be scal able from individuals to work groups, from organizations to communitie s. In addition to laying out the adaptive action framework and clear p rotocols to support it, Glenda H. Eoyang and Royce J. Holladay introdu ce best practices from exemplary professionals who have used adaptive action to meet personal, professional, and political challenges in lea dership, consulting, Alzheimer's treatment, evaluation, education refo rm, political advocacy, and cultural engagement—readying readers to em ploy this new toolkit to meet their own goals with a sense of ingenuit y and flexibility.